Towards a better understanding of yacht cruisers profile for the purpose of a destination development - Ilchuk, Kateryna (2020)
The sea and its use are cross-cutting themes to the political, economic, social and environmental spheres. The uses of marine resources, in particular, the development of nautical tourism, are strategically imperative to Portugal. But this development will only be successful if based on scientific knowledge about the phenomenon. This project is thus presented as the first European research in the deepening of knowledge about yacht cruisers who use the Portuguese coasts. A special emphasis is given to the yachters entering and staying for some time at the marinas and boatyards of the Algarve. From the methodological point of view, this research is based on the primary source of the semi-structured interviews and used qualitative content analysis with the support of the NVivo 9. Yacht cruising, as a distinct niche market, is subjected mainly to senior travellers and their long-term holiday experience. Unlike other tourists, they require a minimum of specialized infrastructure and no accommodation at all. Their main needs are secure place for stops between trips, boat repair and maintenance, food and water supply. The policy makers interested in attracting yacht cruisers tourist category should provide separate facilities from other marine traffic, and by doing so, embrace a small-scale and sustainable form of tourism development which can bring some economic and social advantages to host communities.